2013
DOI: 10.1089/aid.2012.0384
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: High Prevalence of Vitamin D Deficiency in HIV-Infected and HIV-Uninfected Pregnant Women

Abstract: Vitamin D deficiency is common in HIV-infected populations. In resource-limited settings, vitamin D deficiency has been shown to affect HIV disease progression and mortality in pregnant women, and also increases motherto-child HIV transmission and mortality in their infants. This study sought to investigate vitamin D status in HIV-infected women compared to healthy controls in a high-income country setting and determine variables associated with vitamin D deficiency. We prospectively enrolled 40 women/infant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It was found that 25(OH)D concentrations in serum cord blood were <30 ng/mL in 100% of subjects from both groups. The only variables associated with higher serum 25(OH)D concentrations were white race and non-Hispanic ethnicity [ 12 ]. These data agreed with previous observations asserting that vitamin D deficiency not only contributes to HIV disease progression and mortality in HIV-infected pregnant women, but also increases the overall risk of mother-to-child transmission by 46% [ 13 ] and the risk of death in newborns by 61% during follow-up [ 13 ].…”
Section: Prevalence Of Hypovitaminosis D In Hiv-infected Subjectsmentioning
confidence: 99%
“…It was found that 25(OH)D concentrations in serum cord blood were <30 ng/mL in 100% of subjects from both groups. The only variables associated with higher serum 25(OH)D concentrations were white race and non-Hispanic ethnicity [ 12 ]. These data agreed with previous observations asserting that vitamin D deficiency not only contributes to HIV disease progression and mortality in HIV-infected pregnant women, but also increases the overall risk of mother-to-child transmission by 46% [ 13 ] and the risk of death in newborns by 61% during follow-up [ 13 ].…”
Section: Prevalence Of Hypovitaminosis D In Hiv-infected Subjectsmentioning
confidence: 99%
“…Epidemiological data suggest an association between low serum 25(OH)D levels (used to define vitamin D status) and increased risk of adverse women’s reproductive health outcomes [ 12 , 13 ]. Vitamin D deficiency is prevalent in HIV-1-infected women, where upwards of 60% of individuals have levels lower than 50 nmol/L [ 14 ], and is associated with HIV disease progression and mortality [ 15 , 16 ]. A recent phase I clinical trial found enhanced antimicrobial activity in the plasma of HIV-infected individuals following one month of vitamin D supplementation [ 17 ]; however, little is known regarding vitamin D immune-regulation in the female reproductive tract (FRT), or how vitamin D status may impact mucosal HIV acquisition [ 18 ].…”
Section: Introductionmentioning
confidence: 99%